2016
DOI: 10.1590/0103-6440201600427
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of a Root Conditioning Treatment on Periodontally Affected Teeth - An In Vitro Analysis

Abstract: The aim of this study was to evaluated the root surfaces modifications resulted by application of different chemicals agents, and their influence on the fibrin network and fibroblasts attachment. From 96 anterior mandibular human extracted incisor teeth, 192 dentin blocks of buccal and lingual surface were obtained and randomly divided into 6 groups: Cont-control group, which received no treatment; Root surface scaling and root planing (Srp); Citric acid-Srp; EDTA-Srp; Tetracycline capsule-Srp; Tetracycline ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
2
16
1
3
Order By: Relevance
“…The effect of demineralization with sterile water solvent for tetra HCl better than saline solvent, this means that sterile water as a solvent of tetra HCl is more effective for root cementum demineralization. This results was contrast with the findings of the Silva et al 23 study where used saline as the solvent of tetra HCl, who found the residues showed after application on the root surface are probably related to the components present into the capsules, which were not completely dissolved.…”
Section: Discussioncontrasting
confidence: 98%
“…The effect of demineralization with sterile water solvent for tetra HCl better than saline solvent, this means that sterile water as a solvent of tetra HCl is more effective for root cementum demineralization. This results was contrast with the findings of the Silva et al 23 study where used saline as the solvent of tetra HCl, who found the residues showed after application on the root surface are probably related to the components present into the capsules, which were not completely dissolved.…”
Section: Discussioncontrasting
confidence: 98%
“…When epithelial attachment is lost due to periodontitis around teeth, gingival epithelium can be restored with functional BM-attachment to dental root surfaces when the root surface is scaled to expose fresh cementum, on which platelets can form activated aggregates [ 15 , 16 ]. Platelets provide the comprehensive machinery for a fibrin clot in epithelial healing with the proper apico-basal polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, air‐drying desiccation continues to be used in SEM studies of demineralized root surfaces (Bergenholtz & Babay, ; Gamal & Mailhot, ; Silva et al, ; Trombelli et al, ). A comparison of photomicrographs of these reports with other reports which utilized CO 2 desiccation specimen preparation often reveals variations and inconsistencies in expected results.…”
Section: Discussionmentioning
confidence: 99%